HTA of medical devices: Challenges and ideas for the future from a European perspective. Issue 3 (March 2017) - Fuchs, Sabine; Olberg, Britta; Panteli, Dimitra; Perleth, Matthias; Busse, Reinhard
Highlights: Unique overview of European practices and views on HTA of MDs. Further regulatory changes at European level are required to generate adequate clinical data for HTA of MDs. Approaches such as coverage with evidence development should be considered at national level. More alignment of HTA and regulatory processes is needed to improve the current situation. More methodological discussion and collaboration between different stakeholders is indicated. Abstract: Objectives: Health Technology Assessment (HTA) of Medical devices (MDs) and MD-based procedures can be challenging due to the unique features and particularities of this group of technologies, such as device-operator interaction. The aim of this study was to (1) clarify, and supplement earlier findings on European HTA institutions' structural, procedural and methodological characteristics with regard to the assessment of MDs and to (2) capture the institutions' perceptions regarding challenges and future trends. Methods: Semi-structured telephone interviews with 16 representatives from leading European HTA institutions were performed between April and July 2015. Summative and directed content analysis was used for the analysis, which is reported according to the COREQ checklist. Results: Findings from the analysis of the interviews were manifold and partially confirmed what has been noted in the literature (e.g. scarce evidence; identifying relevant studies challenging due to more incremental innovations). Additional themes emerged that can be important for future considerations by HTA institutions and policy-makers alike (e.g. areas for future research; need for specific tools). Conclusions: The collective opinion of 16 European HTA institutions on MD evaluation could provide ideas to ameliorate the current regulatory situation beyond the modified EU regulation and start broader, more in-depth methodological discussions around the issue. Interviewed experts seem to agree that new approaches such as coverage with evidence development as some countries already introduced could help to overcome the problem with scarce evidence.